Activation of the subthalamic region during emotional processing in Parkinson disease. - Kühn, A; Hariz, M; Silberstein, P; Tisch, S; Kupsch, A; Schneider, G; Limousin-Dowsey, P; Yarrow, K; Brown, P (2005)
OBJECTIVE: To elucidate the involvement of the human subthalamic nucleus (STN) region in the processing or transmission of emotional information. METHODS: Local field potentials (LFPs) were recorded from this region in 10 patients with Parkinson disease (PD) undergoing bilateral implantation of the STN for high-frequency stimulation. LFP recordings were made while patients viewed pleasant and unpleasant emotionally arousing and neutral pictures. RESULTS: A significant decrease (event-related desynchronization [ERD]) in the local alpha power (8 to 12 Hz) was found for all stimulus categories starting at about 0.5 seconds after stimulus presentation. However, 1 to 2 seconds poststimulus, the ERD was larger in trials of pleasant (mean ERD: 21.6 +/- 2.8%; p < 0.009) and unpleasant (mean ERD: 15.0 +/- 4.2%; p = 0.018) stimuli compared with neutral stimuli (mean ERD: 4.4 +/- 4.2%). CONCLUSION: The delayed modulation of alpha activity recorded from the area of the subthalamic nucleus in PD may reflect the processing or transmission of information related to emotional stimuli. "Limbic" activation in the region of the subthalamic nucleus may explain why high-frequency stimulation of the subthalamic nucleus alters affect in some patients with PD.